2013
DOI: 10.1093/trstmh/trs087
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C: neglected diseases among health care workers in Cameroon

Abstract: HBV and HCV are neglected diseases among HCW in sub-Saharan Africa. The vaccination rate against HBV was very low at 12.3%, and therefore anti-HBc testing should be mandatory to identify HCW requiring HBV vaccination. Testing for HBV and routine HBV vaccination for HBV-negative HCW should be strongly enforced in Cameroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
25
3
Order By: Relevance
“…The said studies estimated the prevalence rates to be between 0.6% to 21%. In Egypt, the prevalence rate varies between 5.9% and 26.5% [16]. The rate recorded in our study could be due to the age group chosen, that is males aged below 25.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The said studies estimated the prevalence rates to be between 0.6% to 21%. In Egypt, the prevalence rate varies between 5.9% and 26.5% [16]. The rate recorded in our study could be due to the age group chosen, that is males aged below 25.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, the specific median prevalence among subjects under 20 years was 1.3% (22 studies, range: 0% -11%), between 20 and 40 years was 3% (29 studies, range: 0% -28%), and among those over 40 years was 12% (29 studies, range: 0% -55%) [17]. This increase in prevalence with age indicates that the risk of HCV transmission increases over time, and is strongly linked to the use of inadequately sterilized reusable equipment [16]. The rate of co-infection with HBV and HCV in our study population was 0.05%, which is lower than the 0.21% reported by Fouelifack et al in a study conducted in 2012 among blood donors at the Yaounde University Teaching Hospital, and close to the result obtained by Noubiap et al (0.01%) in 2013 among blood donors in Edea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 237 healthcare workers tested in Cameroon, 6.3% were HBsAg-positive and 73.4% anti-HBc-positive, in accordance with the wide spread of HBV infection in this geographical area [60] . Seroprevalence studies conducted in Asia showed varying results.…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 58%
“…The rates of HBsAg and anti-HBc positivity in healthcare workers reported in several studies published in the last three decades [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] range from 0.1% to 8.1% and from 6.2% to 73.4%, respectively, depending on the age of the subjects investigated, the spread of HBV infection in their country of origin and on the prevention strategies used by the healthcare workers (Table 1). Of 5813 healthcare workers tested in Italy in 1985, 21.5% were found to be anti-HBc-positive and 1.8% HBsAg-positive [65] .…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 99%